Extension Strategy for Introducing Private Forestry in a Third World Country: an Illustration with Nigeria - Onweagba, Anthony E. (Indian Forester, 1981)
Forestry contributes about 2.5 per cent of the Gross Domestic Product of Nigeria's economy. The domestic demand for forest products has been projected at 14 per cent by 1985 and by 1995, it is vovisaged that the timber wealth may be depleted if the deforestation practice continues at its present rate. Plantation forestry especially private forestry has been suggested to supplement the maior timber needs of the country as the natural reserves are inadequate to meet the present demand. The paper looks at some steps for a planned change toward the establishment of private forests in Nigeria. Step One, building a relationship, emphasises the contact between the institutional cbange agents and the state forestry staff the clientele, and explains the need for private forestry farming. Step two, diagnosis and resources allocation, examines the potential impact of private forestry on the socio-economic life of the country. It also examines the various alternative resources available to execute the change process. The third step, choosing solution and gaining acceptance for the program, discusses the various methods to orient the pepople with the new idea. It also examines the methods to make the clientele accept the change. The paper concludes with stabilizing the innovation and generating self-renewal. This step strongly recommends the establishment of change agents and extension units within the client system.